2010
DOI: 10.1071/cp10060
|View full text |Cite
|
Sign up to set email alerts
|

Genetic compatibility among domesticated and wild accessions of the tropical tuberous legume Vigna vexillata (L.) A. Rich.

Abstract: Phenotypic similarities and differences between a cultivated variety of the tuberous legume Vigna vexillata from Bali, Indonesia, the putative domesticated variety macrosperma and wild types from Africa, Australia and Indonesia, were reported previously. The present study was undertaken to establish the genetic compatibility of these three accession classes. Seventeen accessions, comprising eight cultivated Bali accessions, one var. macrosperma accession and eight wild accessions from Africa and Austronesia, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
3
13
4
Order By: Relevance
“…However, in our present study, we successfully obtained an F 2 population from a partially fertile F 1 hybrid of a cross between the cultivated zombi pea from Bali using the former as female parent and wild zombi pea, this suggested that the Bali cultivated zombi pea constitutes a primary gene pool with the wild zombi pea. The difference results in our study and that in Damayanti et al [8] is possibly due to environmental factors. Damayanti et al [8] noted that even self-pollination of the cultivated zombi pea from Bali results in low pod setting.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, in our present study, we successfully obtained an F 2 population from a partially fertile F 1 hybrid of a cross between the cultivated zombi pea from Bali using the former as female parent and wild zombi pea, this suggested that the Bali cultivated zombi pea constitutes a primary gene pool with the wild zombi pea. The difference results in our study and that in Damayanti et al [8] is possibly due to environmental factors. Damayanti et al [8] noted that even self-pollination of the cultivated zombi pea from Bali results in low pod setting.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study on reproductive compatibility among cultivated zombi pea from Bali (tuber type zombi pea),cultivated zombi pea from Africa (seed type zombi pea), and wild zombi pea from Africa and Australia revealed no productive incompatibility between the African cultivated zombi pea (seed type zombi pea) and the wild form from both Africa and Australia, but revealed various pre- and post-zygotic compatibilities between the Bali cultivated zombi pea (seed type zombi pea) and the wild form from Africa and Australia [8]. However, in our present study, we successfully obtained an F 2 population from a partially fertile F 1 hybrid of a cross between the cultivated zombi pea from Bali using the former as female parent and wild zombi pea, this suggested that the Bali cultivated zombi pea constitutes a primary gene pool with the wild zombi pea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the two genetic clusters detected in the current study suggest that V. lanceolata is a complex species comprising two closely related taxa or a single species with two different genepools/ population structures; the two taxa/genepools/populations may be related largely to the northern pubescent and var. lanceolata Damayanti et al 2010). The genetic structures reported in these Vigna species were associated with their geographical differences.…”
Section: Genetic Structure Of V Lanceolatamentioning
confidence: 93%